MCOLN1 gene therapy corrects neurologic dysfunction in the mouse model of mucolipidosis IV. Issue 10 (5th April 2021) - DeRosa, Samantha; Salani, Monica; Smith, Sierra; Sangster, Madison; Miller-Browne, Victoria; Wassmer, Sarah; Xiao, Ru; Vandenberghe, Luk; Slaugenhaupt, Susan; Misko, Albert; Grishchuk, Yulia
Abstract: Mucolipidosis IV (MLIV) is an orphan disease leading to debilitating psychomotor deficits and vision loss. It is caused by loss-of-function mutations in the MCOLN1 gene that encodes the lysosomal transient receptor potential channel mucolipin1, or TRPML1. With no existing therapy, the unmet need in this disease is very high. Here, we showed that AAV-mediated CNS-targeted gene transfer of the human MCOLN1 gene rescued motor function and alleviated brain pathology in the MLIV mouse model. Using the AAV-PHP.b vector in symptomatic mice, we showed long-term reversal of declined motor function and significant delay of paralysis. Next, using self-complementary AAV9 clinical candidate vector, we showed that its intracerebroventricular administration in post-natal day 1 mice significantly improved motor function, myelination and reduced lysosomal storage load in the MLIV mouse brain. Based on our data and general advancements in the gene therapy field, we propose scAAV9-mediated CSF-targeted MCOLN1 gene transfer as a therapeutic strategy in MLIV. Graphical Abstract: